Fish Immunology. The modification and manipulation of the innate immune system: Brazilian studies - BILLER-TAKAHASHI,JAQUELINE D. (2014)
The understanding of fish immune system structure and function is essential for the development of new technologies and products to improve productivity. This is the first review on immune system of fish with Brazilian studies. Aquaculture in Brazil has shown massive growth in recent years due to methods of culture intensification. However, these procedures led to disease outbreaks, as well as the chemotherapy and the misuse of antibiotics. A viable alternative to avoid the use of chemicals and prevent economic losses is the administration of immunostimulants and prebiotcs, which act by increasing the innate immune system. In Brazil there is a lack of studies on fish immune system, except by some groups that have studied the effects of the immunostimulants administration in various species.